The Implementation of Peer Teaching Technique in English Teaching at The Eight Grades of Junior High School in Pallangga Gowa - Azis, Suhaeni; Halim, Abdul; Aeni, Nur (Celebes Journal of Language Studies, 2023)
The research used a qualitative method which used descriptive research. The sample consisted of 5 students from the eighth grade of Junior High School at SMPN 5 Pallangga. The data on the implementation of peer teaching techniques were analyzed by using observation and interviews. It aims to investigate the implementation of peer teaching techniques for the students and to explore the advantages and disadvantages of peer teaching for the students. The result of this research showed that the students have a good perception of peer teaching. It can be seen from good based on observations and interviews that have been obtained by the researcher that the students as the peer teacher of English teaching have a good perception of peer teaching. They like to teach by using peer teaching. They like the enjoyable situation of the class on peer teaching. They can also keep good communication with students on peer teaching. The students consider that there are many advantages of peer teaching such as it can increase the teaching experience, the students are more spirited to teach, the students are more confident to teach, it can increase student learning motivation, and it can train the communication skills. So, it can be concluded that the students on peer teaching in English teaching at the eighth grade of junior high school are known good.